The Ministry of the Spirit - Gordon, A. J. (Adoniram Judson), 1836-1895 (Salt Lake City, UT : Project Gutenberg, 2008)
"The Ministry of the Spirit" by A. J. Gordon is a theological treatise written in the late 19th century. This work delves into the role and significance of the Holy Spirit within the context of Christian doctrine, particularly focusing on the time-ministry of the Spirit from Pentecost to the present age. The author's intent is to elucidate the transformative impact of the Holy Spirit on believers and the church, emphasizing the importance of understanding His ministry in relation to Christ and the overall divine plan. The opening of the book sets the stage for a profound exploration of the Holy Spirit$1 (Bs role in Christianity. Gordon reflects on the historical context of the Spirit$1 (Bs work, suggesting that while the Spirit had always been present, His official ministry began at Pentecost, marking a new phase in divine interaction with humanity. The author introduces the concept that the Spirit is not merely an abstract influence but a distinct person of the Trinity with specific roles and powers, aimed at drawing believers closer to Christ. He outlines a clear distinction between the Spirit's ministry before the ascension of Jesus and its current manifestation, suggesting a foundational knowledge of the Spirit is essential for spiritual maturity and effectiveness in Christian life and ministry. (This is an automatically generated summary.)s
Release date is 2008-05-08
E-text prepared by Al Haines
Keywords: Holy Spirit